Guía de capacitación y aplicación de las normas de etiqueta y protocolo en el área secretarial del Gobierno Autónomo Descentralizado Municipal del cantón Quevedo, año 2015 - Loor Bazurto, Yesica Gabriela (2015)
The Autonomous Government decentralized Quevedo Canton, immersed in social, political and economic commitments, requires the active participation of governmental and nongovernmental organizations that promote advice and funding for project implementation and diffusion and dissemination of results. This activity has required the hiring of professional services, expenses for this item and an inactive activity secretarial staff in this context In this sense, the present research has as main objective. To design a training guide and application of standards protocol and etiquette in the secretarial area Decentralized Autonomous Government of the Canton Municipal Quevedo. The results reported that the municipal GAD does not maintain a staff of secretaries with knowledge of etiquette and protocol that ensures efficient attention from external customers (government authorities at local, regional, national and international), which has impacted negatively on institutional image.